2019
DOI: 10.3390/rs11192222
|View full text |Cite
|
Sign up to set email alerts
|

Lidar Prediction of Small Mammal Diversity in Wisconsin, USA

Abstract: Vegetation structure is a crucial component of habitat selection for many taxa, and airborne LiDAR (Light Detection and Ranging) technology is increasingly used to measure forest structure. Many studies have examined the relationship between LiDAR-derived structural characteristics and wildlife, but few have examined those characteristics in relation to small mammals, specifically, small mammal diversity. The aim of this study was to determine if LiDAR could predict small mammal diversity in a temperate-mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Still, we have identified an increase of studies considering other taxonomic groups since the review of [17], including bryophytes, lichens, and fungi (see, e.g., [26,27,89]), a new broad group of organisms increasingly considered in biodiversity conservation and global change research. Studies on mammal group have also increased with successful LiDAR outcomes (see, e.g., [20,21,40,42,66,90,91]. Something similar happened with invertebrates, although to a lesser extent (see, e.g., [12,22,23]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, we have identified an increase of studies considering other taxonomic groups since the review of [17], including bryophytes, lichens, and fungi (see, e.g., [26,27,89]), a new broad group of organisms increasingly considered in biodiversity conservation and global change research. Studies on mammal group have also increased with successful LiDAR outcomes (see, e.g., [20,21,40,42,66,90,91]. Something similar happened with invertebrates, although to a lesser extent (see, e.g., [12,22,23]).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation may be that these metrics are not as standardized as canopy cover and height metrics, so that model outcomes fail to describe this trait. Interestingly, canopy vertical distribution traits were also important for invertebrates (e.g., [12,59]), even for mammals (e.g., [20,42]). All these results support the idea that environmental heterogeneity, measured through the proposed five morphological traits extracted from LiDAR, creates more niches and spatial turnover of species, favoring different habitats and thus allowing more species to coexist in accordance with the habitat heterogeneity hypothesis [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More widely, these methods could be used for evaluating a woodland's importance for biodiversity: the species diversity of birds, for example, is greater in taller, more complex forests with a higher number of layers [86]. Similarly, mammal diversity has been shown to be positively related to LiDAR-derived structural complexity, and negatively related to cover [87]. Forest structure also has a strong control on the speed at which fire spreads through a forest, with structurally complex forests decreasing fire spread [88].…”
Section: Discussionmentioning
confidence: 99%
“…Airborne light detection and ranging (LiDAR) can describe horizontal and vertical vegetation structure across large areas, providing a valuable alternative to the use of intensive field-based methods to assess forest structure (Simonson et al, 2014). Schooler and Zald (2019) demonstrated that LiDAR-derived metrics are effective predictors of small mammal diversity in a temperate mixed-forest community. We therefore used LiDAR and other remotely sensed data to quantify forest structure and predict small mammal occupancy across the landscape.…”
Section: Landscape Variables Characterizing Small Mammal Distributionsmentioning
confidence: 99%